The Role of Accounting Information Systems in Supporting Sustainable Business (Study In Wonosobo Cut Flower MSMEs - Lestari, Fitri Ayu; Wulandari, Hetik; Noviyanto, Puji; Widyawati, Ira Nurviana; Susilowati, Nurdian (Economic Education Analysis Journal, 2021)
The purpose of this study was to examine the business strategy of Micro, Small and Medium Enterprises (MSMEs), the role of accounting information systems in supporting sustainable business, and the constraints on the use of accounting information systems. This type of research was a case study on Cut Flower SMEs in Wonosobo Regency. The sampling technique used purposive sampling with five informants of SMEs, cut flowers of chrysanthemum and kalili. Data collection techniques used documentation studies and in-depth interviews. The collected data was then analyzed by using data analysis developed by Miles and Huberman. MSME actors set a product differentiation business strategy to increase sales turnover. Here, Accounting information systems had a role for business decision making so that investors could include their capital and customer trust. The obstacle to the implementation of the accounting information system was that there was no clear division of tasks between employees and owners so that all business activities were carried out together. This research contributed to the development of sustainable business theory in order to obtain a model of the existence of SMEs during the pandemic that could be used as material for business decision making.